Rancang Bangun Aplikasi Keuangan Untuk Mengatur Jumlah Pengeluaran Pribadi Berbasis Android - Hastedi, Dimas Rian (Politeknik Harapan Bersama, 2024)
Not everyone is able to manage their finances well. Consumptive lifestyles and lack of awareness about the importance of managing finances make a person unable to escape financial problems. In an effort to reduce the impact of existing problems, everyone should have the awareness and effort to manage their finances by recording their financial expenses regularly. In modern times and the rapid development of technology like today, almost everyone has a mobile device at least one Android device. By utilizing existing technology, various things can be done using only their Android devices such as shopping, communicating with someone even though it is quite far away or even to record financial activities. By identifying and collecting data and interviews from related problems, this research aims to be a solution for someone in managing their finances by recording every financial activity in an existing application and making the use of stationery and books to record and recap every expense can be abandoned. With this application, a person can easily record finances anytime and anywhere without fear of losing the notes that have been made. As a result, it is hoped that eating will become wiser and know how much and where the money is spent so that the record can be used as a picture of a person in controlling their money.